Randomized controlled trial of the effect of regular paracetamol on influenza infection. Issue 2 (6th December 2015) - Jefferies, Sarah; Braithwaite, Irene; Walker, Steven; Weatherall, Mark; Jennings, Lance; Luck, Michelle; Barrett, Kevin; Siebers, Robert; Blackmore, Timothy; Beasley, Richard; Perrin, Kyle; ,
Abstract: Background and objective: Anti‐pyretic treatment is recommended in the management of influenza infection. In animal models anti‐pyretic treatment increases mortality from influenza. We investigated the effects of paracetamol on viral and clinical outcomes in adults with influenza infection. Methods: This is a randomized, double‐blind, placebo‐controlled trial of adults aged 18–65 years with influenza‐like illness and positive influenza rapid antigen test. Treatments were 1 g paracetamol four times a day, or matching placebo, for 5 days. Pernasal swabs were taken for influenza quantitative RT‐PCR at Baseline and Days 1, 2 and 5. Temperature and symptom scores were recorded for 5–14 days or time of resolution respectively. The primary outcome variable was area under the curve (AUC) for quantitative PCR log10 viral load from Baseline to Day 5. Results: A total of 80 participants were randomized: no one was lost to follow up, and one withdrew after 4 days. There were 22 and 24 participants who were influenza PCR‐positive in placebo and in paracetamol groups respectively. Mean (SD) AUC PCR log10 viral load was 4.40 (0.91) in placebo and 4.64 (0.88) in paracetamol; difference was −0.24, 95% CI: −0.78 to 0.29, P = 0.36. In all participants there were no differences in symptom scores, temperature, time to resolution of illness and health status, with no interaction between randomized treatment and whether influenza was detected by PCR. Conclusion: Regular paracetamol had no effect on viral shedding, temperature or clinical symptoms in patients with PCR‐confirmed influenza. There remains an insufficient evidence base for paracetamol use in influenza infection. Clinical trial registration:ACTRN12611000497909 at the Australian New Zealand Clinical Trials Registry. Abstract : Despite recommendations to administer paracetamol for symptom relief in influenza and influenza‐like‐illnesses, this study has found that regular administration of paracetamol has no effect on viral or clinical outcomes in this setting. See Editorial, page 207